STATE RECENT ACTION BILLS AS OF 01/01/94 (940101) RHODE ISLAND. RECENT ACTION BILLS REPORT. (Tufts Archival Research Center, 2007)
Report on Rhode Island recent action bills. Lists bills, timelines of bills, and the sponsor and committees for each bill. Includes summaries of some bills.